KESESUAIAN DOKUMENTASI DI LP3I COLLEGE JAKARTA DENGAN STANDARD SISTEM MANAJEMEN MUTU ISO 9001:2008 - Nurdin Nurdin; Wiwiet Prihatmadji (JURNAL LENTERA BISNIS, 2017)
The main steps in order to obtain international certification of ISO 9001 Quality Management System is to prepare the mentality and habits of employees, that is to prepare quality culture as a culture of employees. The next step is the technical preparation, preparing of documents and records, preparations for work process control systems, preparing the performance monitoring and evaluation system, which is summarized in the documentation system of LP3I College. Challenges to the process of implementation of ISO 9001 is overcome by socialization the culture of quality as a work culture in every meeting of the BOD till to the technical meeting daily in the employees or  operators, using the authority of the President Director for any activity in the socialization, training, and implementation of the Quality Management System, making each Head of Department in charge of ISO 9001, arrange the efffectiveness of  internal audit process and making corrective action of any findings of non-conformance and prepared oppotunity for improvement for any observasion findings. The entire process of implementation of ISO 9001 in LP3I College was documented, and controlled accordance to ISO 9001 requirements. Keyword : Quality Management System, ISO 9001:2008